Polygala tenuifolia: a source for anti-Alzheimer's disease drugs - Xinxin Deng; Shipeng Zhao; Xinqi Liu; Lu Han; Ruizhou Wang; Huifeng Hao; Yanna Jiao; Shuyan Han; Changcai Bai (Taylor & Francis Group, 2020)
Context Alzheimer's disease (AD) is a chronic neurodegenerative disease that originates from central nervous system lesions or recessions. Current estimates suggest that this disease affects over 35 million people worldwide. However, lacking effective drugs is the biggest handicap in treating AD. In traditional Chinese medicine (TCM), Polygala tenuifolia Willd. (Polygalaceae) is generally used to treat insomnia, memory dysfunction and neurasthenia. Objective This review article explores the role of P. tenuifolia and its active components in anti-Alzheimer's disease. Methods Literature for the last ten years was obtained through a search on PubMed, SciFinder, CNKI, Google Scholar, Web of Science, Science Direct and China Knowledge Resource Integrated with the following keywords: Polygala tenuifolia, polygalasaponin XXXII (PGS 32), tenuifolin, polygalacic acid, senegenin, tenuigenin, Alzheimer's disease. Results Polygala tenuifolia and its active components have multiplex neuroprotective potential associated with AD, such as anti-Aβ aggregation, anti-Tau protein, anti-inflammation, antioxidant, anti-neuronal apoptosis, enhancing central cholinergic system and promote neuronal proliferation. Conclusions Polygala tenuifolia and its active components exhibit multiple neuroprotective effects. Hence, P. tenuifolia is a potential drug against Alzheimer's disease, especially in terms of prevention.